HISTORY OF THE ACTIVITIES OF MEDICAL INSTITUTIONS IN THE TURKESTAN REGION (Scientific journal of the Fergana State University, 2024)
This article reveals the organization and colonial policy related to the activities of medical institutions in the Turkestan region. In addition to the activities of medical institutions and the attitude of the country's population towards it, the issue of personnel in institutions was also touched upon. The negative aspects of financial and centralized management, which complicate the work of hospitals, are also analyzed.